RELATIONSHIP BETWEEN ANTICARDIOLIPIN AND MULTIPLESCLEROSIS PATIENTS - Mohammad, Haider J; Aboudi, Rana S; Ismaeel, May K (Al-Nahrain Journal of Science, 2009)
The presence of anticardiolipin in serum of multiple sclerosis patients has been reported frequently but no clear relationship between anticardiolipin and the clinical neuroimaging features of multiple sclerosis. To analyze the possible role of anticardiolipin antibody in the pathogenesis of multiple sclerosis. We investigated(22) patients with multiple sclerosis of ages 25-45 years. The patients were also compared with(20) healthy individuals.We found there was a highly significant elevation in the concentration of IgG and IgM anticardiolipin antibody in patient with multiple sclerosis than in control group P < 0.001.The prevalence of IgG and IgM anticardiolipin antibody was 36.4% and 27.3% respectively.There was a highly significant difference between study groups. The findings of this preliminary study show that increased levels of anticardiolipin IgG and IgM associated with exacerbations of multiple sclerosis.The significance of this association in the pathogenesis of multiple sclerosis remains unknown.